Lightning strokes and its effects on historical monuments, heritage properties and important landmarks a detailed perspective of traditional and scientific methods of lightning protection systems - Sreedhar, Srisailam; Srinivasan, Venkatesh (International Journal of Engineering and Technology, 2018)
Lightning is one of the inevitable disastrous natural phenomena which present serious threat to tall structures including ancient monuments and electrical systems. Though researchers have carried out a wide gamut of research studies to analyze the extent of damage due to direct lightning strikes on important buildings and structures, the focus of this research is on understanding the effects of lightning on tall structures of historical importance and landmark monuments of significance. In this context, different types of Lightning Protection Systems (LPS) are being used to protect tall structures from lightning flashes. However, several complexities related to the appropriate choice of LPS continue to confront researchers since characteristics of lightning such as stroke current, striking distance, return stroke modelling, geometry of the structure etc. pose considerable challenges. This research study presents a detailed chronological overview of lightning strikes on ancient structures, cause and effects, review on LPS strategies along with its impacts on tall structures, historical monuments and landmarks. In addition, a detailed analysis based on a specific case study of a typical historical monument is carried out to ascertain the critical significance of the stipulated zone of protection essential for historical monuments and various risks involved during implementation.